Scheduling method and scheduling system - Yamashita Koichiro; Yamauchi Hiromasa; Otomo Toshiya; Suzuki Takahisa; Kurihara Koji (2017)
A scheduling method includes determining whether priority of an application to be activated is of a given priority, the determining being performed by a first data processing apparatus that is included in a first group having at least one data processing apparatus; transferring to a second data processing apparatus that is included in any one among a second group and the first group, a predetermined function of the first data processing apparatus so as to execute the application by the first data processing apparatus, the transferring being performed when the priority of the application is of the given priority, and the first and the second groups being among a plurality of groups that each includes at least one data processing apparatus; and placing the application in an execution queue of the first data processing apparatus, when the priority of the application is not the given priority.